Wer macht die Materialwende?: Zur Rolle von zirkulären und denkmalpflegerischen Ansätzen für die Transformation des Bauwesens - Johannes Warda; Georg Schiller; Barbara Ditze; Robert Knippschild (TATuP – Zeitschrift für Technikfolgenabschätzung in Theorie und Praxis)
The transition to a circular economy involves a long-term transformation of the construction industry. Recent successes in research and development are counteracted by the sluggishness of the construction sector and other obstacles to implementation. However, decisions that minimize the consumption of resources and the climate impact of construction can be made immediately – especially by keeping existing buildings in use for as long as possible or revitalizing vacant buildings. The practical expertise for this can be found in the field of historic preservation. Like no other discipline, it focuses on recording and evaluating the inventory and has strategies and methods for long-term preservation. Previously a niche area limited to an exclusive portfolio, preservation principles can be fruitfully applied to all construction tasks as part of a circular building economy.